(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
During our research, we obtained a number of interesting information. The village of Qamay is distinguished from other villages in some respects, namely, when a person from the Kun’gorat clan dies, they definitely make a new coffin for him and then take him to the grave and bury him. Another such example is that the relatives did not give anything during the funeral. Since the 40s, giving money has become a traditional ritual.